Strategies for translating Arabic similes in Al- Manfaluti's Al-Abrat into English - Talal Zahrawi, Rasha M.; Syed Abdullah, Syed Nurulakla; Mustapha, Nik Farhan; Redzuan Abdullah, Muhammad Alif (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper presents a comprehensive analysis of the English translation techniques applied to Arabic similes in Mustafa Lutfi al-Manfaluti's seminal work, "Al-Abrat." Utilising Pierini’s (2007) theoretical framework, the study examines the complexities and nuances involved in translating Arabic similes into English, focusing on the translation by Majid Khan Malik Siddiqui. The research methodically analyses a selection of 200 similes from the book, exploring the various strategies employed in the translation process. The study reveals a predominant use of literal translation, reflecting a strong commitment to maintaining the integrity of the original text. Additionally, it discusses the role of creative adaptation and simile reduction in addressing cultural and linguistic challenges, emphasising the translator’s role as a cultural mediator. The findings contribute to the understanding of translation practices in literary contexts, highlighting the importance of cultural and contextual awareness in the translation of figurative language. This paper underscores the significance of translation in bridging linguistic and cultural divides, enriching the appreciation of Arabic literature in the English-speaking world.